The impact of social assistance on households’ transfer behavior: A micro data analysis - Kristina, Anita; Rasyid, Mohtar; Purwanti, Putu Ayu Pramitha (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2023)
This paper investigates whether public transfers crowd-out inter-household transfers in Indonesia. Using household data from Indonesia Family Life Survey (IFLS-3 & IFLS-4), this study evaluates the impact of direct cash transfer programs (Bantuan Langsung Tunai, BLT) on inter-family transfer (i.e., monetary transfer from parents, siblings, child, and other family members who do not live co-residently). The results indicate that, in general, the crowding-out effect is relatively small. This effect is statistically significant only in urban households but not rural ones. This finding suggests that expanding public transfer under formal social security programs to cover poor households does not significantly reduce the existence of informal transfers. Further, public transfers potentially improve the distribution of household income.